1978
DOI: 10.1126/science.567374
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Mutagens in Beef and Beef Extract During Cooking

Abstract: Mutagens, distinguishable from benzo[a]pyrene and from mutagenic amino acid and protein pyrolysis products, are formed when ground beef is cooked in a home hamburger cooking appliance or when beef stock is concentrated, by boiling, to a paste known commercially as beef extract. "Well-done" hamburgers contain about 0.14 part per million of the mutagens, and beef bouillon cubes which contain beef extract about 0.1 part per million. Since such mutagens may be potentially carcionogenic and are formed during ordina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0
1

Year Published

1982
1982
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 248 publications
(38 citation statements)
references
References 8 publications
2
35
0
1
Order By: Relevance
“…This is in line with the report that effect of charred meat depends, to a greater degree, on the details of processing (Felton andKnize, 1990 andCommoner, 1978). It is likely that the naturally occurring nitrosamine in meat, when subjected to charcoal fire roasting, could be raised to a concentration toxic enough to cause alteration in morphology of tissues of liver and pancreas and perhaps other organs.…”
Section: Discussionsupporting
confidence: 74%
“…This is in line with the report that effect of charred meat depends, to a greater degree, on the details of processing (Felton andKnize, 1990 andCommoner, 1978). It is likely that the naturally occurring nitrosamine in meat, when subjected to charcoal fire roasting, could be raised to a concentration toxic enough to cause alteration in morphology of tissues of liver and pancreas and perhaps other organs.…”
Section: Discussionsupporting
confidence: 74%
“…The formation of mutagens detectable by the Ames test upon broiling dried fish and ground meat was reported by us (9) and Commoner et al (10). These *National Cancer Center, 1-1, Tsukiji 5-chome, Chuo-ku, Tokyo 104, Japan.…”
Section: General Backgroundmentioning
confidence: 88%
“…A year later Commoner and his coworkers deduced that the elevated background of revertants found with the standard Ames/Salmonella mutagenesis assay was due to the beef extract used to grow the bacterial culture (2). It was also noted by this group and by Felton and Nebert (3) a few years earlier that metabolizing enzymes were needed for this increased background.…”
Section: Introductionmentioning
confidence: 88%
“…It was also noted by this group and by Felton and Nebert (3) a few years earlier that metabolizing enzymes were needed for this increased background. It was also found that other cooked beef products such as hamburger had mutagenic constituents (2). Since these early findings our laboratory has examined various cooked protein food sources for mutagenicity and we have found mutagenic activity in extracts of muscle of beef, lamb, chicken, pork, and fish (4).…”
Section: Introductionmentioning
confidence: 98%